Management of hepatitis B infected pregnant women: a cross-sectional study of obstetricians - Stephanie D. Chao; Chrissy M. Cheung; Ellen T. Chang; Allison Pei; Samuel K. S. So (BMC, 2019)
Abstract Background Our study aims to describe how obstetricians manage pregnant women infected with chronic hepatitis B in a region with a large high-risk population. Methods We performed a cross-sectional study among practicing obstetricians in Santa Clara County, California. All obstetricians practicing in Santa Clara County were invited to participate in the study. Obstetricians were recruited in person or by mail to complete a voluntary, multiple choice survey on hepatitis B (HBV). Survey questions assessed basic HBV knowledge and obstetricians' self-reported clinical practices of the management of HBV-infected pregnant women. Pooled descriptive analyses were calculated for the cohort, as well as, correlation coefficients to evaluate the association between reported clinical practices and hepatitis B knowledge. Results Among 138 obstetricians who completed the survey, 94% reported routinely testing pregnant women for hepatitis B surface antigen (HBsAg) with each pregnancy. Only 60.9% routinely advised HBsAg-positive patients to seek specialist evaluation for antiviral treatment and monitoring and fewer than half (48.6%) routinely provided them with HBV information. While most respondents recognized the potential complications of chronic HBV (94.2%), only 21% were aware that chronic HBV carries a 25% risk of liver related death when left unmonitored and untreated, and only 25% were aware of the high prevalence of chronic HBV in the foreign-born Asian, Native Hawaiian and Pacific Islander population. Obstetricians aware of the high risk of perinatal HBV transmission were more likely to test pregnant women for HBV DNA or hepatitis B e-antigen in HBV-infected women (r = 0.18, p = 0.033). Obstetricians who demonstrated knowledge of the long-term consequences of untreated HBV infection were no more likely to refer HBV-infected women to specialists for care (r = 0.02, p = 0.831). Conclusion Our study identified clear gaps in the practice patterns of obstetricians that can be readily addressed to enhance the care they provide to HBV-infected pregnant women.